Age-related alterations in efferent medial olivocochlear-outer hair cell and primary auditory ribbon synapses in CBA/J mice - Dörje, Nele Marie; Shvachiy, Liana; Kück, Fabian; Outeiro, Tiago F.; Strenzke, Nicola; Beutner, Dirk; Setz, Cristian (Frontiers in Cellular Neuroscience, 2024)
Introduction: Hearing decline stands as the most prevalent single sensory deficit associated with the aging process. Giving compelling evidence suggesting a protective effect associated with the efferent auditory system, the goal of our study was to characterize the age-related changes in the number of efferent medial olivocochlear (MOC) synapses regulating outer hair cell (OHC) activity compared with the number of afferent inner hair cell ribbon synapses in CBA/J mice over their lifespan.Methods: Organs of Corti of 3-month-old CBA/J mice were compared with mice aged between 10 and 20 months, grouped at 2-month intervals. For each animal, one ear was used to characterize the synapses between the efferent MOC fibers and the outer hair cells (OHCs), while the contralateral ear was used to analyze the ribbon synapses between inner hair cells (IHCs) and type I afferent nerve fibers of spiral ganglion neurons (SGNs). Each cochlea was separated in apical, middle, and basal turns, respectively.The first significant age-related decline in afferent IHC-SGN ribbon synapses was observed in the basal cochlear turn at 14 months, the middle turn at 16 months, and the apical turn at 18 months of age. In contrast, efferent MOC-OHC synapses in CBA/J mice exhibited a less pronounced loss due to aging which only became significant in the basal and middle turns of the cochlea by 20 months of age.Discussion: This study illustrates an age-related reduction on efferent MOC innervation of OHCs in CBA/J mice starting at 20 months of age. Our findings indicate that the morphological decline of efferent MOC-OHC synapses due to aging occurs notably later than the decline observed in afferent IHC-SGN ribbon synapses.